1989
DOI: 10.1152/ajpregu.1989.256.1.r120
|View full text |Cite
|
Sign up to set email alerts
|

Two-phase change of sympathetic rhythms in brain ischemia, Cushing reaction, and asphyxia

Abstract: The present study was designed to determine the extent to which the brain stem neural networks, normally capable of synchronizing the sympathetic nerve discharge (SND) into 2- to 6- and 10-Hz rhythmic fluctuations, contribute to the control of autonomic reactions during brain hypoxia and/or hypercapnia. Vertebral, cardiac, and renal nerve discharges were recorded electrophysiologically in 34 anesthetized, curarized, and artificially ventilated cats. The sympathetic nerve responses to cerebral ischemia (elicite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…Other investigators also showed that SN activity increases under different circumstances such as hypoxia, high intracranial pressure and hemor- Fig. 4 rhagic hypotension (13)(14)(15). These reports parallel our finding of increased SN activities.…”
Section: Discussionsupporting
confidence: 90%
“…Other investigators also showed that SN activity increases under different circumstances such as hypoxia, high intracranial pressure and hemor- Fig. 4 rhagic hypotension (13)(14)(15). These reports parallel our finding of increased SN activities.…”
Section: Discussionsupporting
confidence: 90%
“…Systems having both linear and non-linear functions and exhibiting transitions between different states are not infrequent in the nervous system (Freeman, 1975). In the sympathetic networks, functionally relevant phase transitions were described during cerebral ischaemia when the rhythmic SND turned into high-frequency desynchronized discharge (Kocsis et al 1989(Kocsis et al , 1993 and in the awake cat, where a switch between the 2-6 Hz random activity and a stable 10 Hz oscillation occurs, associated with specific behaviours (Ninomiya et al 1989). This latter transition also occurred spontaneously in decerebrate cats (Cohen & Gootman, 1970;Barman et al 1992) and under the effect of anaesthetics (Gootman & Cohen, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Postganglionic sympathetic nerve activity was recorded from the central ends of the cut left vertebral (VN), inferior cardiac (CN) and renal nerves (RN) simultaneously, as described earlier (Kocsis, Fedina & Pasztor, 1989; Kocsis et al 1993). The nerve signals were amplified with differential amplifiers with a bandpass of 1P5 Hz to 1P5 kHz and, together with the arterial blood pressure, were stored on magnetic tape for off-line computer analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also previously described that such hypertensive BP waves were associated with more severe neonatal illness 2. Many of the neural and endocrine controls of the cardiovascular system have intrinsic rhythms which may be exaggerated by hypoxia 3. Repeated measurements of neonatal endocrine function are scarce due to technical and ethical difficulties; however arginine vasopressin has previously been demonstrated to induce BP waves 4…”
Section: Discussionmentioning
confidence: 99%